Canine Ischemic Dermatopathy - Clinical and Laboratory Follow-up - Ferreira, Tiago Cunha; Fábio Ranyeri Nunes Rodrigues,; Hélio Noberto de Araújo Júnior,; Carlos Donato Barbosa Alves Júnior,; Diana Célia Sousa Nunes Pinheiro, (Acta Scientiae Veterinariae, 2024)
Background: Canine ischemic dermatopathy poses an increasing challenge in Veterinary Dermatology, stemming from compromised cutaneous blood supply, resulting in skin lesions due to inadequate oxygen and nutrient delivery. Treatment strategies involve enhancing blood flow, pain management, and wound healing, necessitating vigilant monitoring of inflammatory control and therapy-related side effects. This study aims to present a comprehensive clinical and laboratory follow-up of 2 cases of canine ischemic dermatopathy. Cases: The 2 cases involved a 2-year-old Pitbull weighing 19.5 kg and a 3-year-old Mongrel bitch weighing 5.0 kg, both presenting widespread alopecic and crusting lesions. Blood samples were collected for hemato-biochemical (D0, D30 and D60 (case 1) and D0, D21 and D45 (case 2) and serological exams for Leishmaniasis, along with cutaneous cytology (ear tips) and biopsy for histopathological analysis. Hemato-biochemical analysis revealed leukocytosis with an elevated neutrophil count, and seronegativity to Canine Leishmaniasis. Cytological and histopathological analyses confirmed the diagnosis of canine ischemic dermatopathy, revealing a pyogranulomatous inflammatory process and characteristic skin alterations. Treatment strategies were customized for each case, with the Pitbull initially treated with pentoxifylline (10 mg/kg) and prednisolone (1.5 mg/kg) and later transitioned to oclacitinib (0.4 mg/kg), resulting in improved clinical signs and hemato-biochemical parameters. The Mongrel bitch exhibited substantial skin recovery and reduced inflammatory biomarker levels following oclacitinib (0.4 mg/kg) therapy. Discussion: The report offers a comprehensive account of the clinical and laboratory monitoring of 2 bitches with canine ischemic dermatopathy. The primary clinical hallmark of this ailment is the development of widespread alopecic and crusted lesions, prompting diagnostic consideration in the patient under discussion, supported by the clinical history and complementary examinations. Histological and cytological assessments confirmed the characteristics indicative of ischemic dermatopathy, while systemic leukocyte analysis highlighted an inflammatory state attributed to the skin lesions. Immunomodulators formed the basis of therapy in both cases. However, the Pitbull did not exhibit a complete clinical response, necessitating a transition from pentoxifylline to oclacitinib. Post-treatment hemato-biochemical evaluations demonstrated a gradual reduction in the systemic inflammatory process. Attention is drawn to the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and albumin to globulin ratio (AGR) as these cost-effective biomarkers offer insights less susceptible to pathophysiological variations compared to individual analyses. These parameters are increasingly recognized for their potential in monitoring chronic inflammatory diseases. Following clinical and hematological improvement, the frequency of oclacitinib was initially reduced from BID to SID. However, a recurrence of lesions prompted a reinstatement of oclacitinib in a BID regimen. This report presents a comprehensive clinical and laboratory follow-up of canine ischemic dermatopathy in 2 bitches and notably introduces the utilization of NLR, PLR, and AGR for monitoring therapeutic progression in this context. Encouragement is given for further studies and reports exploring the application of these biomarkers in monitoring this disease. Keywords: canine ischemic diseases, bitch, neutrophil to lymphocyte ratio, systemic inflammation